THU0075 The relationship between disease activity and disability is mediated by pain and fatigue in early rheumatoid arthritis. (15th June 2017) - Twigg, S; Hensor, EMA; Emery, P; Morgan, AW; Tennant, A; ,
Abstract : Background: Disability in early rheumatoid arthritis (RA) is correlated with disease activity. However, the relationship between these two clinical outcomes is relatively under-investigated. Understanding how disability is driven by disease activity will allow targeted interventions to improve function in early RA, alongside the suppression of inflammation. Objectives: To identify mediators in the relationship between disease activity and disability in early RA. Methods: Cases with new consultant-made diagnoses of RA were recruited to Yorkshire Early Arthritis Register within 24 months of symptom onset. At the baseline assessment, clinical variables were collected including the 3 variable disease activity score from counts of 28 tender and swollen joints and C-reactive protein (DAS28), Health Assessment Questionnaire (HAQ) and visual analogue scores (VAS) of pain and fatigue. Structural equation models (SEM) were constructed to evaluate the relationship between DAS28, HAQ, pain, symptom duration (SD), age and fatigue. Results: Of 721 cases included, 482 were female and 239 male. Median age was 58 for both genders and median HAQ was 1.25 and 1.00 for women and men, respectively. A path model within a SEM framework (Figure 1 ) was a good fit to the data (Chi square 7.528, df=6, p=0.2748; CFI 0.997; RMSEA 0.027). However, the model could not be applied simultaneously to both genders; although estimates of regression coefficients did not vary between males and females (metric invariance), model intercepts were different. In earlier models, age was not a significant predictor and regressions of fatigue on DAS28 were not significant: the effect of DAS28 upon fatigue was fully mediated by pain. Standardised coefficients of direct and indirect effects of DAS28 on HAQ are shown in Table 1, together with Sobel tests for significance of mediator variables. The greatest effect upon HAQ was the direct effect from DAS28, but some of the effect of DAS28 on HAQ was partially mediated by pain. Furthermore, the effect of pain upon HAQ was also partially mediated through fatigue. According to the Sobel test, pain and fatigue were significant mediators in both females and males. Conclusions: DAS28 dominates the impact upon HAQ in early RA; pain is shown to be an important mediator of the effects of DAS28 on HAQ, while fatigue is important as a mediator of the effect of pain on HAQ. This adds to previous evidence that pain is a driver of fatigue in RA (1) and suggests that interventions to manage pain could be important adjuncts to supression of inflammation in early RA, in order to optimise function. References: Druce KL, Jones GT, Macfarlane GJ, Basu N. (2015) Arthritis & Rheumatology, 67: 2303. Disclosure of Interest: None declared